2000
DOI: 10.1091/mbc.11.11.3993
|View full text |Cite
|
Sign up to set email alerts
|

A Fission Yeast Homolog of Int-6, the Mammalian Oncoprotein and eIF3 Subunit, Induces Drug Resistance when Overexpressed

Abstract: Through a screen to identify genes that induce multi-drug resistance when overexpressed, we have identified a fission yeast homolog of Int-6, a component of the human translation initiation factor eIF3. Disruption of the murine Int-6 gene by mouse mammary tumor virus (MMTV) has been implicated previously in tumorigenesis, although the underlying mechanism is not yet understood. Fission yeast Int6 was shown to interact with other presumptive components of eIF3 in vivo, and was present in size fractions consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 38 publications
(46 reference statements)
6
68
0
Order By: Relevance
“…This could reflect a direct interaction between the two complexes, or alternatively an influence of eIF3 on other events required for 60S joining, such as GTP hydrolysis by eIF2 (Merrick, 1979). In agreement with our results, fission yeast strains lacking eIF3e are viable, and polysome profile analysis showed that they have no major defects in translation initiation (Bandyopadhyay et al, 2000;Crane et al, 2000), though a decreased level of de novo protein synthesis was detected by pulse labeling in a more recent study (Udagawa et al, 2008). Fission yeast eIF3e and eIF3m define two distinct eIF3 complexes that may promote the translation of different sets of mRNAs; the eIF3m complex associated with bulk cellular mRNAs, whereas the eIF3e-containing complex associated with a far more restricted set (Zhou et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could reflect a direct interaction between the two complexes, or alternatively an influence of eIF3 on other events required for 60S joining, such as GTP hydrolysis by eIF2 (Merrick, 1979). In agreement with our results, fission yeast strains lacking eIF3e are viable, and polysome profile analysis showed that they have no major defects in translation initiation (Bandyopadhyay et al, 2000;Crane et al, 2000), though a decreased level of de novo protein synthesis was detected by pulse labeling in a more recent study (Udagawa et al, 2008). Fission yeast eIF3e and eIF3m define two distinct eIF3 complexes that may promote the translation of different sets of mRNAs; the eIF3m complex associated with bulk cellular mRNAs, whereas the eIF3e-containing complex associated with a far more restricted set (Zhou et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Cancer cells overexpressing BCL-XL are generally resistant to a wide range of anticancer drugs (Minn et al, 1995), suggesting that breast cancer cells with high eIF3e expression might be inherently resistant to therapy as a result of increased BCL-XL translation. Interestingly, eIF3e was previously isolated through its ability to induce multidrug resistance when overexpressed in fission yeast (Crane et al, 2000). Although this model organism lacks BCL-2 family proteins, eIF3e was proposed to target selectively mRNAs required for protective cellular stress responses (Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This event weakly modifies general translation, but induces sensitivity to various drugs such as caffeine (Bandyopadhyay et al, 2000;Akiyoshi et al, 2001). Conversely, overexpression of Schizosaccharomyces pombe Int-6 causes resistance to caffeine, similar to what has been observed for the Poh1 (Rpn11) subunit of the proteasome (Spataro et al, 1997;Crane et al, 2000). It has also been shown that depletion of Int-6 in S. pombe affects spore formation and causes weak chromosome segregation defects (Bandyopadhyay et al, 2000;Yen and Chang, 2000).…”
Section: Introductionmentioning
confidence: 63%
“…An Int6 homolog was found in ®ssion yeast (Bandyopadhyay et al, 2000;Crane et al, 2000). The yeast Int6 protein was found strongly associated with 40S ribosomal particles suggesting a common role with mammalian Int6 in translation initiation.…”
Section: Discussionmentioning
confidence: 99%